2018
DOI: 10.1021/acs.joc.8b00953
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Post-Ugi Ipso-Cyclization with Switchable Diastereoselectivity

Abstract: A gold-catalyzed post-Ugi ipso-cyclization for the diastereoselective synthesis of spirocyclic pyrrol-2-one-dienone system is described. Tuning the catalytic system, solvent, and temperature allowed selectively attaining two sets of diastereoisomers. The scope of the process has been evaluated, and a putative mechanistic model was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 89 publications
1
26
0
1
Order By: Relevance
“…Two diastereomeric dienones were isolated depending on both the gold-catalyst and the reaction conditions. Taking the 140 yields into account and supported by a conformational theoretical analysis, the authors concluded that the isomer 140a resulting from the catalytic treatment with Ph 3 PAuCl is energetically more favorable than that derived from the bulkier JhonPhosAuCl precatalyst ( 140b ) (Nechaev et al, 2018). A related work had been previously published by the same group (He et al, 2017).…”
Section: Gold-catalyzed Isomerization Processes Involving An Initimentioning
confidence: 99%
“…Two diastereomeric dienones were isolated depending on both the gold-catalyst and the reaction conditions. Taking the 140 yields into account and supported by a conformational theoretical analysis, the authors concluded that the isomer 140a resulting from the catalytic treatment with Ph 3 PAuCl is energetically more favorable than that derived from the bulkier JhonPhosAuCl precatalyst ( 140b ) (Nechaev et al, 2018). A related work had been previously published by the same group (He et al, 2017).…”
Section: Gold-catalyzed Isomerization Processes Involving An Initimentioning
confidence: 99%
“…Peshkov, Van der Eycken, and co-workers, in 2018, reported a very unique diastereoselective-switchable transformation of Ugi adducts 93a, obtained from the reaction of alkynoic acid, aldehydes, aminophenols, and isocyanides in methanol. 272 It was demonstrated that when Ugi adducts 93a were subjected to a cationic gold(I) catalyst the ipso-cyclization products such as spirocyclic pyrrol-2-one-dienones 93b and 93c can be efficiently obtained (Scheme 93). More importantly, the diastereoselectivity of these reactions was effectively controlled by varying the electronic and steric properties of ligands, the nature of the counteranion, as well as the solvent, temperature, and catalyst loading.…”
Section: Ligand-dependent Divergent Gold Catalysis (Ldgc)mentioning
confidence: 99%
“…The same principle, both for the production of the substrates by Ugi MCR and the Au-mediated cycloisomerization was reported by Peshkov and Van der Eycken (Scheme 135, part B). 241 In this case, ortho-amino phenol derivatives 585 were employed thus allowing the formation of spirolactams 586 in which the carbonyl is formed α to the spiro center. Interestingly, two catalytic systems were employed, each allowing the selective formation of one of the two diastereoisomers.…”
Section: Alkynyl Carbonyl Derivativesmentioning
confidence: 99%
“…It was also shown that an Ugi MCR allowed for the rapid synthesis of diverse N -substituted lactams that could be readily cyclodearomatized under gold catalysis (see 584 ). The same principle, both for the production of the substrates by Ugi MCR and the Au-mediated cycloisomerization was reported by Peshkov and Van der Eycken (Scheme , part B) …”
Section: Carbon π-Systems With Electron-withdrawing Groupsmentioning
confidence: 99%